2022
DOI: 10.1177/03611981211062893
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Train Derailments in Canada through Process Safety Techniques and Insights into Enhanced Safety Management Systems

Abstract: Canada’s rail transportation network is a critical part of Canada’s integrated supply chain which connects industries, consumers, and resource sectors to ports on the Atlantic and Pacific coasts. One transportation activity that is essential to most industries, especially oil and manufacturing, is the rail transport of dangerous goods (DG). Although rail transportation of DG is beneficial to Canada’s economy, not paying attention to the safe transportation of these types of goods can have irreparable effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(64 reference statements)
0
2
0
1
Order By: Relevance
“…A study done by Kyriakidis et al ( 30 ) identified distraction/loss of concentration, safety culture, proper communication between employees, workload, training, and stress as the most significant contributors to the operators’ performance in the rail industry. Esmaeeli et al ( 31 ) discussed some of the appropriate strategies that can be implemented to reduce the employees’ errors. For instance, conducting regular team meetings to strengthen teamwork ( 32 ), providing practical training alongside the online training ( 33 ), and regular assessment of employees’ competencies to ensure that individuals are capable of properly applying their knowledge in practice.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Kyriakidis et al ( 30 ) identified distraction/loss of concentration, safety culture, proper communication between employees, workload, training, and stress as the most significant contributors to the operators’ performance in the rail industry. Esmaeeli et al ( 31 ) discussed some of the appropriate strategies that can be implemented to reduce the employees’ errors. For instance, conducting regular team meetings to strengthen teamwork ( 32 ), providing practical training alongside the online training ( 33 ), and regular assessment of employees’ competencies to ensure that individuals are capable of properly applying their knowledge in practice.…”
Section: Discussionmentioning
confidence: 99%
“…The level of water near a railway track is a major factor affecting the safety of train passage and cargo, and current monitoring techniques are limited in spatial and temporal coverage. Railway operators need to identify the development of problematic water levels in the area surrounding the track in a timely manner to avoid incidents that can potentially cost human life and damage the environment [9]. Current inspection methods in Canada, include visual observations by trained inspectors walking/driving along the track to identify indications of water problems.…”
Section: Introductionmentioning
confidence: 99%
“…С каждым годом в реализации этого процесса все больше места отводится различным автоматизированным программам, позволяющим не только проектировать изделия с учетом обеспечения прочности, но и полностью разрабатывать технологии их изготовления [1][2][3]. Тем не менее случаи выхода из строя изделий или даже возникновения аварийных ситуаций происходят достаточно часто [4][5][6]. Как правило, для установления объективных причин наступления таких инцидентов назначают проведение металлографической экспертизы (МЭ).…”
Section: Introductionunclassified